A Model for Implementing Good School Governance in the Supervision of Islamic Education in Sebangau Kuala Subdistrict, Pulang Pisau Regency - Anam, Muhamad Abdul; Pelu, Ibnu Elmi A. S. (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze and develop a model for implementing Good School Governance (GSG) to enhance the effectiveness of supervision in Islamic Religious Education. A quantitative approach with an explanatory design was employed. Data were collected via a questionnaire administered to 150 respondents, comprising Islamic Religious Education teachers, school principals, and supervisors in Sabangau Kuala Subdistrict, Pulang Pisau Regency. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study indicate that all dimensions of GSG namely transparency, accountability, participation, responsibility, and independence, have a positive and significant effect on the effectiveness of PAI supervision. Accountability is the variable with the most dominant influence. The research model exhibits strong explanatory power with an R-square value of 0.682, indicating that GSG accounts for the majority of the variation in supervisory effectiveness. These findings confirm that integrating the principles of good school governance into the supervisory system can enhance the quality of planning, implementation, evaluation, and follow-up of supervision on an ongoing basis. Theoretically, this study enriches the body of research on Islamic education management based on governance. Practically, this study provides recommendations for policymakers to optimize GSG-based supervision. This study recommends the development of further studies with a broader geographical scope and a mixed-methods approach to obtain more comprehensive results.